Drawing on the Teachings of the Ming Taizu: The East-West Allusions in Han Lin’s “The Book of the Bell” from the Late Ming Catholic Tradition - LEE, Ling Hon (Journal of Research for Christianity in China (JRCC), 2025)
No Abstract